Homogalactanas sulfatadas da alga Codium isthmocladum com atividade anticoagulante - Farias, Eduardo Henrique Cunha de (2006)
Since the first description of sulfated polysaccharides from seaweeds, the biological activities of these compounds have been evaluated under different aspects and experimental procedures. Among the broad biological activities presented by seaweed polysaccharides, anticoagulant action appears as a promising function. In this present study we have obtained sulfated polysaccharides from the green seaweed Codium isthmocladium by proteolytic digestion, followed by separation into five fractions (0.3, 0.5, 0.7, 0.9 and 1.2) by sequential acetone precipitation. The chemical analyses have demonstrated that all fractions are composed mainly by sulfated polysaccharides. The anticoagulant activity of these fractions was determined by activated partial thromboplastin time (aPTT) and prothrombin time test (PT) using citrate normal human plasma. None fraction has shown anticoagulant activity by PT test. Furthermore, all of them have shown anticoagulant activity by aPTT test. These results indicated that the molecular targets of these sulfated polysaccharides are mainly in the intrinsic via of the coagulation cascade. Agarose gel electrophoresis in 1,3-diaminopropane acetate buffer, pH 9.0, stained with 0.1% toluidine blue showed the presence of two or three bands in several fractions while the fraction 0.9 showed a single spot. By anion exchange chromatography, the acid polysaccharides from the 0.9 acetone fraction were separated into two new fractions eluted respectively with 2.0 and 3.0 M NaCl. These compounds showed a molecular weight of 6.4 and 7.4 kDa respectively. Chemical analyses and infrared spectroscopy showed that Gal 1 and Gal 2 are sulfated homogalactans and differ one from the other in degree and localization of sulfate groups. aPPT test demonstrated that fractions 2,0 and 3,0M (Gal1 and Gal 2, respectively) have anticoagulant activity. This is the first time that anticoagulant sulfated homogalatans have been isolated from green algae. To prolong the coagulation time to double the baseline value in the aPTT, the required amount of sulfated galactan 1 (6,3mg) was similar to low molecular heparin Clexane®, whereas only 0,7mg of sulfated galactan 2 was needed to obtain the same effect. Sulfated galactan 2 in high doses (250mg) induces platelet aggregation. These results suggest that these galactans from C. isthmocladum have a potential application as an anticoagulant drug